Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan Dan Kualitas Audit Terhadap Nilai Perusahaan - Erfana, Agus Pungki; Dwijayanty, Rima (Universitas Sangga Buana, 2024)
Company value is an investor's perception of the success rate of a company which is often associated with the stock price. A high stock price makes the company's value also high, and can increase market confidence not only in the company's current performance but also in the company's prospects in the future upcoming. Corporate value is also related to the image of the company itself. The better the company's image in the public, the higher the company's value. This studyaims to examine the effect of profitability, reliability, company size, and audit quality on company value. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The method used is a quantitative method with an explanatory research approach. The sampling method using non-random sampling, namely purposive sampling and using secondary data in the form of annual reports and company financial statements, was obtained by 63 companies with a five-year period, the study obtained 315 observations. Data analysis technique using Panel Data Regression Analysis with EViews 12 program application with a significance level of 5%. The results showed that profitability, leverage, company size have a positive and significant influence on the value of the company. As for the audit quality variable, it has no effect on the value of the company.